252 Effects of Increasing Urea in Corn Silage Diets and Duration of Ensiling on the Rumen Undegradable Protein Content of Corn Silage - Spore, Tyler (J Anim Sci, 2021)
Two experiments were conducted to evaluate the effects of increasing urea in a corn silage cattle diet and ensiling time (ET) impact on rumen undegradable crude protein (RUP) content of corn silage. In Exp. 1, ten ruminally- and duodenally cannulated heifers (body weight 265 ± 16 kg) were utilized in a 4 × 4 Latin square design and treatments were urea included at 0, 0.5, 1, or 1.5% of dietary dry matter (DM). In Exp. 2, corn silage samples were collected during feedout at 32-d intervals from the time of ensiling (d 0) to 160 d post-ensiling followed by separation in water to forage and grain components. Forage and grain samples were ruminally incubated in two steers to calculate RUP content of corn silage. In Exp. 1, DM intake increased linearly from 5.7 to 6.8 kg/d as urea inclusion increased (P < 0.001). Apparent total tract digestibility of DM and organic matter increased linearly from 55.8% to 60.8%, and 60.1% to 64.9%, respectively (P < 0.001). Total tract digestibility of neutral and acid detergent fiber increased linearly with increasing urea inclusion (P ≤ 0.004). In Exp. 2, the RUP content of the corn grain component decreased from 43.7% of CP at day 0 to 15.8% and 10.0% of CP after 32 and 96 d of ensiling, respectively (quadratic, P < 0.01). The RUP content of the forage averaged 19.3% of CP across ET ranging from 21.5 to 17.8% of CP (P ≥ 0.28). Estimated from the individual components, the RUP content of whole corn silage decreased from 32% to 17.1% of CP after 160 d in storage, a portion of which is digestible. Urea supplementation improved digestibility of corn silage diets and RUP content of corn silage decreased with storage time, primarily driven by changes in the corn grain component.